CURATIVE AND PROPHYLACTIC CONTROL OF FUNGAL LEAF ROT COMPLEX IN ROOT (WILT) AFFECTED COCONUT PALMS IN INDIA - N. Srinivasan; M. Gunasekaran (International Coconut Community Journal, 2003)
Root wilt disease (RWD) is a debilitating malady of coconut in India that is caused by phytoplasma. In RWD affected palms, leaf rot disease (LRD) is commonly superimposed. The LRD is due to fungi and this leaf rot phase forms an integral part of RWD complex. Control of LRD is important as it severely disfigures the palm and brings about rapid deterioration in its health and productivity. Control trial involving Phytosanitation of young leaves, pouring of broad spectrum - systemic fungicide, Contaf 5 E (Hexaconazole 5% EC) into the axil of spindle leaf besides a number of other measures was conducted to study their ameliorating effect on LRD. Prophylactic control trial, especially with the broad-spectrum fungicides was also conducted. Pouring of Contaf into the axil of spindles along with phytosanitory measures on the spindle and other young leaves significantly reduced the incidence of LRD in newly emerging spindles effecting cure. Application of the fungicide on RWD palms prior to the onset of LRD, offered prophylactic protection to emerging leaves against LRD. Relevance of practising integrated control measures, cure of LRD at an early stage itself, the need for strict adoption of crop management technology etc. for effective disease control are highlighted here.